A Probabilistic Approach to Injection‐Induced Seismicity Assessment in the Presence and Absence of Flow Boundaries - S. M. Hosseini; T. H. W. Goebel; B. Jha; F. Aminzadeh (Geophysical Research Letters)
Abstract Induced seismicity models that do not account for the effects of flow boundary conditions and uncertainty in initial stresses on the seismicity rate fail to predict the seismicity observed in real‐world injection sites. We present a model for the probabilistic assessment of induced seismicity that incorporates in situ stresses, pressure, and reservoir boundary conditions. The model considers a randomly distributed network of faults undergoing frictional failure due to pressure‐induced effective stresses. A semianalytical method is used to capture the effect of flow boundary conditions on pressure and seismicity rate based on pressure diffusion and Mohr‐Coulomb failure. We compare the model predictions with induced seismicity observations in Paradox Valley and German Continental Deep Drilling Program. We demonstrate that differences in the flow boundary conditions can drastically change the seismic response to injection. The strongest difference is observed for a closed boundary reservoir for which the induced seismicity rate increases exponentially.